The Limits of Europeanization - Featherstone, K. author. aut Link
XVIII, 247 p.
Keywords: An innovative case study of one of the most recalcitrant member states of the EU: Greece. Based on extensive empirical research, the book relates its evidence to two major conceptual frames: 'Europeanization' and 'varieties of capitalism'. These are complementary and one compensates for the limitations of the other.